Diferenças na alimentação de Rhamdia quelen em quatro diferentes ordens de sistemas lóticos - Villares Junior, G. A. [UNESP]; Goitein, R. [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to compare the food composition of Rhamdia quelen in four distinct order rivers. It was performed at a low part at the basin of the Sorocaba river in systems classified as first (Anastácio stream), second (Nego stream), fifth (Tatuí river) and sixth (Sorocaba river) orders. Collections were performed every month between January and December of 2011. The stomach contents were examined by using the alimentary index (IAi) and compared by the non-parametric method non-metric multidimensional scale ranking (NMDS) with the Spearman rank correlation. A diet difference was observed for individuals of the smaller systems (Anastácio and Nego streams) and the larger ones (Tatui and Sorocaba rivers), represented respectively by allochthonous and autochthonous organisms compounding their diets. Marginal vegetation and its interaction with the water conditions may respond to these composition differences.
Differences in the feeding of Rhamdia quelen (Siluriformes, Heptapteridae) in four distinct lotic systems
Keywords: Alochthonous items; Atlantic; Autochthonous items; Opportunist fish; Rain Forest; Sorocaba river basin